Kuwait During the Years OF The Collapse of The Pearl Diving in The First Half of The Twentieth Century - alfaris, Mohammed faris (Al-Adab Journal, 2022)
The expansion of the artificial pearls trade in the Arab Gulf markets led to the breakdown of the oldest profession that the inhabitants of the region worked in for hundreds of years.This didn’t only affect the people who used to work on diving for pearls, but it also affected every field that was connected to this trade in a way or another such as the complementary professions, the merchants, and the local and foreigner markets.The breakdown of New York stock market in 1929 that the pearls trade was a part of led to the complete collapse of this trade and profession.Kuwait, that was famous for its huge fleets of pearls, was the country that was harmed the most by this breakdown. Subsequently Kuwait witnessed very hard years during the thirties of the twentieth century and the years of World War II which expanded from 1939 to 1945.The class of merchants collapsed and the problem of unemployment prevailed among the members of the society and the natural pearls trade witnessed a great depression as nobody wanted to buy it.